PARTICIPATION OF NON-GOVERNMENTAL NON-PROFIT ORGANIZATIONS IN THE IMPLEMENTATION OF NATIONAL ENVIRONMENTAL PROGRAMS OF UZBEKISTAN - Саидова Ш. Ш (TARIXIY TADQIQOTLAR, 2026)
The article presents the history of the development of non-governmental nonprofit organizations in the field of ecology and environmental protection in Uzbekistan. Their role and influence on the formation and gradual development of environmental policy in the country are analyzed. The ecological spheres and directions and the periods when their role were strengthened, as well as a result of which reforms these changes took place, are revealed.